Social Class Conflict Presented In â€œThe Kite Runnerâ€ Novel Based On Marxism Theory - Rubiyanto, Yohanes Eko; Arini, Restu ((JELE) Journal Of English Language and Education, 2016)
The writer conducts the research related to class conflict which is presented in Khaled Hosseiniâ€™s â€œThe Kite Runnerâ€ novel. This qualitative research is written to analyze the conflicts that happen in Afghan society which is mainly caused by difference of social class. The research is conducted by using library research. The method used in this research is descriptive qualitative method as the data are described in the form of sentences. The steps of collecting the data in this research are reading both the novel and the supporting theories related, analyzing, organizing and displaying the data to allow conclusions to be drawn. The results show that the society in the twentieth is fundamentally separated by two large groups namely Pashtun and Hazara. They are inhabit Afghanistan as told in The Kite Runner. The Pashtuns act as the dominant upper class and the Hazaras fill the society of the lower class which fits the theory of Marxism.